New chromosome number and unreduced pollen formation in Achillea species (Asteraceae) - Sheidai, M.; Azanei, N.; Attar, Farideh (Acta Biologica Szegediensis, 2009)
Cytological studies were performed in 14 populations of 8 Achillea species growing in Iran. A. eriophora, A. tenuifolia, A. oxyodonta, A. talagonica and A. biebersteinii showed 2n = 2x = 18 chromosome number, A. wilhelmsii and A. vermicularis showed 2n = 4x = 36 and A. millefolium showed 2n = 6x = 54 chromosome number. The chromosome numbers of A. eriophora and A. talagonica are new to science and new polyploidy levels are reported for A. tenuifoli and A. wilhelmsii. Tetraploid and hexaploid species, they formed only bivalents in metaphase of meiosis-I showing diplontic behavior possibly due to allopolyploid nature of the species studied and the presence of control over pairing among homologous chromosomes. Multipolar cells were observed almost in all populations and species studied leading to the formation of abnormal tetrads and pollen grains as well as unreduced (2n) pollen formation.